Twisting somersaults - Yeadon, M. R. (SB & MC, 2015)
The origins of this book date back to 1968 when Yeadon tooked up trampolining at age of 22 at the instigation of Neville Huskisson, a man of many talents. Having the remnants of a mathematical background (BA, MA Cantab) he soon became interested in the mechanics of initiating twist after takeoff and used Neville for the experimental verification of theoretical deductions. Huskisson was able to demonstrate that a full twist to the left or the right could be produced after takeoff in a forward somersault dive from the one-metre springboard by a suitable choice of asymmetrical arm movement. In 1969 at a Loughborough University summer school directed by Syd Aaron it became evident that a sustained aerial twist could also be produced using asymmetrical hip movements as in, for example, a rudi-out fliffus which has no twist in the first somersault and 1.5 twists in the second somersault. This interest eventually lead to a PhD in 1985 on the Mechanics of Twisting Somersaults and a career change from mathematics teacher to sports biomechanics researcher. The PhD thesis gave rise to nine journal papers which form the core of this book and are reproduced here by the kind permission of the publishers. An important consideration when writing a book is to consider the target readership, taking note that every equation used is likely to narrow the appeal and reduce the number of potential readers. As the reader will note there is an abundance of equations, especially in the early chapters, so this text is unlikely to become a best seller. On the other hand there is valuable information for practitioners of the various relevant sports, particularly in the simulation examples presented in the applications chapter. As a consequence the book should be of interest to coaches and competitors in the sports of trampolining, diving, gymnastics, tumbling and freestyle skiing as well as to students of biomechanics, applied mathematics and physics.